Is there “Black Panther” Movement in Israel? Protests of Ethiopian Jews - Sources of Conflict and Policy Implications - Gurstein, Benjamin Binyamin (International Journal of Humanities and Social Science Research, 2019)
The migration of various ethnic groups creates a challenge for policymakers in general and civil society in particular. The concerns, as well as maintaining the status quo, could present obstacles in creating a homogenous and equitable civil society. As an immigrant-absorbing state, Israel is challenged both socially and economically in these realms. The Melting Pot concept was one of Israel’s founding blocks since the 1950’s fail. Has it failed? Is there truth to the protesters’ allegations of institutionalized racism? In light of the demonstrations and accusations of racism in Israeli society, what changes should be set in motion?